Haematological parameter among drug resistant tuberculosis patients in Ibadan (2024)
Background: Haematological abnormalities are common among tuberculosis patients but there is dearth of information on their value as prognostic markers in Multidrug resistant tuberculosis patients. This study examined the association between complete blood count variables and drug resistant tuberculosis. Materials and methods: Nighty (90) consenting adults comprising 30 Drug Resistant Tuberculosis patients (DR-TB), 30 Drug susceptible tuberculosis patients (DS-TB) and 30 healthy participants were recruited in this study. Ethical approval was obtained from Oyo State Ministry of Health Institutional Review Board while patients' demographic data were collected using structured questionnaire. Five milliliters (5mL) of blood samples were collected in EDTA bottle. Haematological parameters were analysed using impedance technique and Mindary-BG5380 5-part automated system. Result: The mean hemoglobin levels were significantly lower in DR-TB patients (11.70 ± 2.73 g/dL) than in DS-TB patients (8.33 ± 9.56 fL), with a mean difference of -3.37 ± 12.29 g/dL. The mean MCH and MCHC levels were also slightly lower in DR-TB patients (26.17 ± 3.44 pg and 30.41 ± 1.92 g/dL, respectively), but the differences were not statistically significant. The WBC count was similar in both groups (8.20 ± 3.80 × 109 /L and 8.45 ± 3.63 × 109 /L, respectively). Conclusion: The mean hemoglobin levels were significantly lower in DR-TB patients than in DS-TB patients which may be due to the increased inflammation associated with DR-TB. The WBC count was similar in both groups, suggesting that the immune system is responding similarly to the infection in both DR-TB and DS-TB patients. Recommendation: In the meantime, healthcare providers should be aware of these potential differences and use them to inform their diagnosis and treatment of patients with tuberculosis. Keyword: Haematological parameters; drug resistant tuberculosis; Ibadan. DOI: https://dx.doi.org/10.4314/ahs.v24i1.3 Cite as: Adewole PD, Ogundipe TD, Alabi SO, Nuhu A. Haematological parameter among drug resistant tuberculosis patients in Ibadan. Afri Health Sci, 24 (1). 10-15. https://dx.doi.org/10.4314/ahs.v24i1.3 cases worldwide are resistant to at least one anti-TB drug. The emergence of drug resistant tuberculosis (DR-TB) In the year 2021, 450,000 cases of multidrug-resistant TB